Analisis Butir Soal Pilihan Ganda Materi Lingkup Kerja Akuntansi dan Keuangan Lembaga Menggunakan Anates - Ainiyah, Nisa Nur; P, Andini Nathaniela N; A, Muhammad Falah Avicena; Hakim, Luqman; Pratiwi, Vivi (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
This research aims to assess the quality of the questions using the Anates application, in order to determine the suitability of the questions for testing. This assessment is carried out by examining various indicators such as validity, reliability, level of difficulty, distinguishability, and quality of distractors, which are important parameters in evaluating the quality of test items. The method used is documentation with a survey research approach via the Quiziz application. This research was carried out at SMK YPM 1 Taman involving class X students majoring in Accounting as research subjects, with 10 students acting as respondents. The data collection technique was carried out using multiple choice questions totaling 15 items, which included material about accounting and institutional finance. The results of the question analysis show a reliability value of 0.58 and a correlation of 0.41, which indicates that the question has a fairly good level of validity.